Non-viral in vivo electroporation-based chromosomal engineering and repair assessment in the murine uterine epithelium - Satoru Iwata; Yumi Miura; Takashi Iwamoto (PLoS ONE, 2026)
Chromosomal rearrangements generated by CRISPR/Cas systems are valuable for studying genomic architecture and repair mechanisms. However, most in vivo approaches rely on viral vectors, which require specialised production, prolonged nuclease expression, and elevated biosafety containment. Here, we applied Cas9 ribonucleoprotein (RNP) electroporation to the murine uterine epithelium as a simple, non-viral strategy for somatic chromosomal engineering. This method successfully induced defined interchromosomal translocations at multiple loci and enabled the molecular assessment of large-scale inversion repair (57.8 Mb) using paired gRNAs with an ssODN donor. While rearranged alleles were detected at low apparent frequencies in bulk uterine DNA—consistent with epithelial-restricted delivery and somatic mosaicism—high-depth whole-genome sequencing (WGS) and PCR provided nucleotide-resolution confirmation of precise junction formation. Our findings demonstrate that uterine electroporation of CRISPR RNPs is a feasible, rapid approach for evaluating engineered chromosomal rearrangements in vivo , providing a controlled platform for analyzing somatic DNA repair outcomes without viral confounds.